Bovine Serum Albumin (BSA)/polyacrylonitrile (PAN) biohybrid nanofibers coated with a biomineralized calcium deficient hydroxyapatite (HA) shell for wound dressing - Homaeigohar, Shahin; Tsai, Ting Yu; Zarie, Eman S.; Elbahri, Mady; Young, Tai Horng; Boccaccini, Aldo R. (Materials Science and Engineering C, 2020)
Here, for the first time, a nanofibrous (NF) wound dressing comprising biomineralized polyacrylonitrile (PAN) nanofibers is developed. In contrast to the majority of the currently available nanofibrous wound dressings that are based on natural polymers, PAN is a synthetic, industrial polymer, which has been rarely considered for this purpose. PAN NFs are first hydrolyzed to allow for tethering of biofunctional agents (here Bovine Serum Albumin (BSA)). Later, the biofunctionlized PAN NFs are biomineralized by immersion in simulated body fluid (SBF). As a result, core-shell, calcium deficient hydroxyapatite (HA)/BSA/PAN nanofibers form, that are mechanically stronger (elastic modulus; 8.5 vs. 6 MPa) compared to the untreated PAN NFs. The biomineralized PAN NFs showed promising bioactivity as reflected in the cell biology tests with fibroblast and keratinocyte cells. Hs68 fibroblasts and HaCat keratinocytes were found to be more viable in the presence of the biomineralized NFs than when they were co-cultured with the neat PAN NFs. Such mechanical and biological characteristics of the biomineralized PAN NFs are favorable for wound dressing applications.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Biofunctionalization; Biomineralization; Nanofiber; Polyacrylonitrile (PAN); Wound dressing